Aplikasi Etika Ekonomi Islam Dalam Sektor Perdagangan Dan Jasa - Putria, Uus; Nasrudin, Nasrudin (STAI Siliwangi Bandung, 2016)
Islamic Economics is an economic system which main goal is to realize justice and prosperity equally. The principle of Islamic economics is the prime norms that build Islamic economic structures or frameworks extracted from the Qur'an and / or Sunnah. This economic principle serves as a basic guideline for each individual in behaving economically, so that people reach falah both in the field of trade and services.Trade is primarily activity ofCompanies which are engaged in trading. The purpose of trading is to improve the welfare of human life, so that in trading it is needed principles of Islamic economic ethics to achieve these objectives, so it can be distinguished which must be applied in trading and which are prohibited in Islam. Likewise, in the field of services that area lot of types that the application is measured by the principle of qualityservice.